Soluble gp350/220 and deletion mutant glycoproteins block Epstein-Barr virus adsorption to lymphocytes. - Tanner, J (1988)
The Epstein-Barr virus (EBV) major outer envelope glycoprotein complex, gp350/220, was known to be a ligand for CR2, a B-lymphocyte plasma membrane protein. By Scatchard analysis, soluble EBV gp350/220 binds with high affinity (KD, 1.2 x 10(-8) M) to approximately the same number of B-lymphocyte surface sites as do CR2-specific monoclonal antibodies. Soluble gp350, gp220, or an amino-terminal, 576-amino-acid gp220 derivative binds similarly to B-lymphocyte receptors. Soluble gp350/220, gp220, or even a 470-amino-acid, amino-terminal gp220 derivative blocks EBV adsorption or infection. These experiments demonstrate that (i) gp350/220 is the predominant or exclusive EBV ligand for B lymphocytes; (ii) ligand-receptor blockade can prevent lymphocyte infection by EBV; and (iii) the amino-terminal, 470-amino-acid domain of gp350/220 contains the key ligand domain(s). Consistent with the ligand domain(s) being in the amino-terminal half of gp220 are the findings that the gp350/220-specific, EBV-neutralizing monoclonal antibody 72A1 blocks EBV adsorption by recognizing an epitope in the amino-terminal 470 (probably within the amino-terminal 162) amino acids and a deletion of amino-terminal amino acids 28 and 29 from gp350/220 inactivates ligand activity.